2013
DOI: 10.1002/cmdc.201300438
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine NMR‐Based Screening on Cell Membrane Extracts

Abstract: The possibility of measuring the action of inhibitors of specific enzymatic reactions in intact cells, cell lysates or membrane preparations represents a major advance in the lead discovery process. Despite the relevance of assaying in physiological conditions, only a small number of biophysical techniques, often requiring complex set‐up, are applicable to these sample types. Here, we demonstrate the first application of n‐fluorine atoms for biochemical screening (n‐FABS), a homogeneous and versatile assay bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
1
8
0
Order By: Relevance
“…The results clearly showed that the proposed n-FABS method was successful in detecting strong inhibitors of FAAH activity in cells. Also, it allowed the accurate quantification of the corresponding IC 50 values, all of which were consistent with those obtained in previous work but measured in cell membrane extracts [46].…”
Section: Ligand-observed Protein Binding Interactionssupporting
confidence: 87%
“…The results clearly showed that the proposed n-FABS method was successful in detecting strong inhibitors of FAAH activity in cells. Also, it allowed the accurate quantification of the corresponding IC 50 values, all of which were consistent with those obtained in previous work but measured in cell membrane extracts [46].…”
Section: Ligand-observed Protein Binding Interactionssupporting
confidence: 87%
“…hFAAH overexpressing HEK293 cells hFAAH-overexpressing HEK293 (hFAAHeHEK293) cells were obtained as described previously [30]. The cells were cultured at 37 C in a humidified incubator (5% CO 2 ) using Dulbecco's modified Eagle's medium (DMEM; EuroClone, code ECB7501L) containing 10% fetal bovine serum, 1% L-glutamine, and 1% penicillinestreptomycin (complete DMEM).…”
Section: Methodsmentioning
confidence: 99%
“…where [30]. The selected fragments were tested at 200 mM and displayed different levels of inhibition (see Fig.…”
Section: N-fabs Assay Validation and Ic 50 Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, titration with an inhibitor of the enzyme permits one to determine the IC 50 value (the inhibitor concentration at which 50% inhibition of the reaction is observed), based on the difference in the 19 F resonance intensity in the initial state and the enzyme-modified state. Such experiments can be modified for other purposes, including simultaneous screening against multiple proteins, determining the function of a newly sequenced protein, and for screening in living cells or cell extracts (Dalvit, Ardini, Fogliatto, Mongelli, & Veronesi, 2004;Dalvit et al, 2003;Forino et al, 2005;Frutos, Tarrago, & Giralt, 2006;Lambruschini et al, 2013;Veronesi et al, 2014).…”
Section: F Nmr-based Biochemical Screeningmentioning
confidence: 99%